Evidence of High-Risk Human Papillomavirus in Esophageal Cancer in East Azerbaijan Province, Northwest of Iran. (7th January 2022) - Sadeghian, Zahra; Bannazadeh Baghi, Hossein; Poortahmasebi, Vahdat; Sadeghi, Javid; Hasani, Alka; Azadi, Arezoo; Ahangar Oskouee, Mahin
Abstract : Background . Human papillomavirus (HPV) is one of the most important viral agents associated with several classes of cancers in humans. The aim of this study was to investigate HPV in esophageal cancer in the East Azerbaijan province, northwest of Iran. Methods . 140 paraffin-embedded specimens of esophageal tissues were investigated using nested-polymerase chain reaction (nested-PCR) with primer designing for the L1 region of HPV genome. According to the pathological diagnosis, the samples were divided into two groups: 70 patients with esophageal cancer EADC ( n  = 35) and ESCC ( n  = 35) as the case group and those without tumour in esophagus tissue as a control ( n  = 70). Results . HPV DNA was isolated from 20 (28.57%) of the 70 paraffin-embedded tissue specimens of esophagus cancer. Of these, 6 cases (17.14%) of EADC and 14 cases (40%) of ESCC were positive. In contrast, all cases of the control group were negative for the HPV genome. Sequence analysis revealed that HPV types 16 and 18 are the most frequent ones identified in this study. Conclusion . The prevalence of HPV in esophageal cancer can vary depending on the geographical location and other factors. Based on the findings of this study, HPV infection may possibly have contributed to an increased risk of esophageal cancer in a group of patients in Tabriz.